The wooing of Earth - Dubos, René J. (René Jules) 1901-1982 (New York Charles Scribner's Sons, 1980)
Examines man's relationship to nature from an historical and biological perspective, discusses the destruction of many of the world's ecosystems, and suggests methods for reversing damage that has been done to the natural world
A family of landscapes-- The wilderness experience-- Can the world be saved?-- The resilience of nature-- Humanization of the earth-- The management of earth-- Of places, parks, and human nature-- Humankind and the earth-- Appendices-- Notes-- Index.
LG-21188, donated by Atty. Antonio A. Oposa Jr.
Keywords: Landscape protection; Nature conservation